Panoramic view of Front Street, Dawson, Yukon Territory, August 17, 1899. - Goetzman, H. J.
PH Coll 246.324 [Meed journal: "Panorama 2 ft. 6 in. in length backed with linen in roll form. Illustrates a scene on Aug. 17, 1899 on the Front Street of Dawson, Y.T. 8" from the left end is the dock (in course of construction) of the Canadian Development Co. of which company I was then the Dawson agent. The Yukon Dock was built in 1900 on the adjoining site (viewed toward the photographer). That dock concern was promoted, part-owned and managed by me until it was sold. Then the two docks were consolidated with the river steamboat fleet of the Canadian Development Co. and the White Pass & Yukon Railway, to complete the transportation system known as the White Pass & Yukon Route."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number